2022
DOI: 10.3390/medicina58030451
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria for Metabolic Syndrome in High-Altitude Regions: A Systematic Review

Abstract: Background and Objectives: Metabolic syndrome (MS) has many risk factors that are important to investigate in populations living at sea level and in high-altitude geographic regions. The aim was to identify the components of MS that cross-sectional studies use to assess in adult populations residing in high-altitude regions. Materials and Methods: A systematic review study was conducted. The Pubmed database was used. The search for original articles (cross-sectional) was performed from January 2013 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
1
0
1
Order By: Relevance
“…There is limited evidence on the correlation between altitude and metabolic syndrome, as most studies focused on metabolic profiles among people living at high altitudes [25] without comparing metabolic syndrome at different altitudes. Only one cross-sectional study involving 260 Ecuadorians has shown an inverse correlation between metabolic syndrome and altitude [26].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…There is limited evidence on the correlation between altitude and metabolic syndrome, as most studies focused on metabolic profiles among people living at high altitudes [25] without comparing metabolic syndrome at different altitudes. Only one cross-sectional study involving 260 Ecuadorians has shown an inverse correlation between metabolic syndrome and altitude [26].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This study applied the International Diabetes Federation (IDF) criteria. ATP-III and IDF use blood pressure, some indicator of obesity, HDL cholesterol, triglycerides and serum glucose as components, which are the most frequently used components in cross-sectional studies to measure MetS in the population living at high altitudes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Este estudio aplicó los criterios de la International Diabetes Federation (IDF). ATP-III e IDF usan como componentes a la presión arterial, algún indicador de obesidad, colesterol HDL, triglicéridos y glucosa sérica; los cuales son los componentes más frecuentemente usados por estudios transversales para medir SM en población residente en elevadas altitudes 6 .…”
Section: Introductionunclassified